IMPLEMENTASI KEBIJAKAN PELAYANAN PERUSAHAAN DAERAH AIR MINUM KABUPATEN BANGGAI - Yada, Rahman (Katalogis, 2016)
This study aims to determine how the implementation of policies on local water companies Banggai. The research method is a descritive study with a qualitative approach, in which data and information collected using a Likert scale and interviews with selected informants. Theory used in this research is theory of George C. Edwars III to see aspect of communication in which policies are implemented properly, the clues not only understood but also be clear. Aspect of human resources and infrasructure resources adequate. Aspect tendency(disposition), which received the support of the implementation is the policy. Aspect bureaucratic structure which is one of the body as whole is implementing the policy. Research shows that: Still less intensive communication carried on the difference in views between leaders and employes of PDAM, which could an obstacle in implementation of policies in the services of PDAM. Available resources both facilities and infrastucture, and the resources have not been adequate apparatus to support the implementation of services policies in the taps. Disposition or attitude implementor inconsistent in sanctions for customers. Bureaucratic structure not be optimal, it is ironically standard operating procedures (SOP) yet.